Violência sexual e debate de gênero: avaliação em profundidade da rede de enfrentamento à violência contra a mulher no município de Fortaleza/CE - Duda, Rayane Lima (2023)
There are several forms of violence that historically affect women in Brazilian society. The understanding of the phenomenon is broad, as it mobilizes thinking about structural aspects that maintain forms of violation, oppression and domination. Recent data point to important evidence on sexual violence and its impact on the lives of women who are victims of this type of crime. In view of this, the research proposed here has as its central theme the analysis of the problem of rape of women in the context of the evaluation of public policies, understanding the gaps left by the State with regard to the debate on gender and sexual violence. Therefore, its general objective is to evaluate the coping actions developed by the network to combat violence against women in the context of the city of Fortaleza. To this end, the study is characterized as qualitative research, making use of techniques such as literature review and document analysis; and lists In-Depth Evaluation as an evaluative approach, establishing specific objectives in line with the axes of this perspective, which are: evaluating the content of the National Policy for Combating Violence Against Women (NPCVAW), verifying its conceptual and theoretical bases and its internal coherence, paying attention to what is stated about sexual violence; analyze the context in which the NPCVAW was formulated, compiling data on the political moment and socioeconomic conditions in which it was formulated; investigate the institutional trajectory of the Assistance Network for Women in Situations of Violence in Fortaleza, capturing the directions for combating sexual violence, in order to identify the degree of coherence/dispersion of the program throughout its journey through institutional channels; and analyze the temporal and territorial spectrum of NPCVAW, aiming to compare its general objectives with local specificities and their historicity. Through the research it was possible to perceive the permanent invisibility of the issue of sexual violence against women, which also revealed the weaknesses of the National Policy for Combating Violence against Women (NPCVAW) and especially the Network for Combating Violence Against Women in Fortaleza /CE. The study found that this invisibility normally occurs from two perspectives: the first, that of statistics. It is hard work to find specific data on sexual violence committed against women. Most studies are generally divided between domestic violence against women or rape of vulnerable people. The second approach is the one that hides the intersectional nature of the problem. Both with regard to victims of sexual crimes and perpetrators, it is difficult to find data on race, class, sexual orientation, etc. The judicial system does not pay due attention to this data and scientific production is still scarce, which ends up camouflaging the set of intersectional determinations that are intertwined with this problem.